Controllership Functions: an analysis in the Brazilian scenario - Lunkes, Rogério João; Schnorrenberger, Darci; Rosa, Fabricia Silva da (Review of Business Management, 2013)
The definition of basic functions is one of the key points in the consolidation of any field of knowledge, as the controllership. However, there are difficulties in this regard due to unsatisfactory concepts and principles, confusing and sometimes contradictory literature. Therefore, this study aims to identify and analyze the functions of the controllership in empirical studies, and in books and reference manuals. To achieve this goal, major works and reference manuals were selected, besides articles published in leading accounting journals and conferences. The results show an increase in the release of new works and the publication of empirical studies about controllership. Among the functions consolidated in terms of books and manuals, as well as empirical studies, the following can be highlighted: planning, control, accountancy, and report elaboration and interpretation.